PEMBERIAN WASIAT WAJIBAH TERHADAP ANAK TIRI MENURUT HUKUM WARIS ISLAM INDONESIA (STUDI PUTUSAN NOMOR 1581/PDT.G/2020/PA.PBR) : Granting A Mandatory Will For Step Children According To Indonesian Islamic Heritage Law (Study Ruling Number 1581/Pdt.g/2020/Pa.Pbr) - Ivan Aldwin Pasaribu; Khairani Bakri (Faculty of Law, Universitas Trisakti, 2024)
Islamic Inheritance Law as regulated in the Al-Quran and Hadith as well as the Compilation of Islamic Law determines that the heirs who inherit are the husband or wife left behind, children, parents and siblings. A stepchild is a child bor.n as a result of a marriage between one husband or wife and the previous wife or husband. Pekanbaru Religious Court Decision No. 1581/Pdt.G/2020/PA.Pbr states that stepchildren receive a mandatory will. So, the formulation of the problem in this research is whether a mandatory will can be given to stepchildren according to Indonesian Islamic Inheritance Law and whether the judge's decision number 1581/Pdt/G/202/Pa/Pbr which gives a mandatory will to stepchildren is in accordance with inheritance law in Indonesia. The type of research used is descriptive normative research using secondary data where conclusions are drawn deductively. The results of the research explain that stepchildren do not receive a mandatory will, this is because it is not in accordance with Indonesian Islamic Inheritance Law and the judge's decision is contrary to Article 209 of the Compilation of Islamic Law.